Transformasi Manajemen Pondok Pesantren Menuju Pesantren Digitalisasi Di Tengah Tantangan Globalisasi - Khatipah, Khatipah; Arifin, Samsul; Sumarsi, Sumarsi; Faifatur R, M. Kurma Nur; Faruq, H. Muhammad Khalid (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2025)
This study highlights the modernization efforts undertaken by the Cahaya Islam Islamic Boarding School in responding to changing times, especially due to the influence of globalization and the development of digital technology. In this era, educational institutions including Islamic boarding schools can no longer rely solely on traditional methods; they need to adopt new approaches in management, such as digitalization of administration, use of online platforms for learning, and technology-based information systems. However, these updates must not eliminate the main roots of Islamic boarding schools, namely noble values ​​such as sincerity, humility, morals, and spirituality. This means that even though Islamic boarding schools are starting to use technology, the values ​​that have been the characteristics and strengths of Islamic boarding schools are still maintained and used as the main guidelines. This is a challenge as well as an opportunity, how to combine modernity with tradition so that Islamic boarding schools remain relevant, develop, and do not lose their identity. This transformation still pays attention to Islamic boarding school values ​​such as sincerity, manners, and togetherness. The key to its success lies in the role of wise Islamic boarding school leaders and the support of all elements, including teachers and students, in understanding and managing technology in an Islamic way. The results of the study show that digital transformation is not a threat, but an opportunity for Islamic boarding schools to develop and become pioneers of change amidst global challenges. The Cahaya Islam Islamic Boarding School is an example that modernization can go hand in hand with preserving tradition.